Корреляция теплового потока земли и нефтегазоносности – фундаментальная закономерность Западной Сибири - Галиева М. Ф. Маргарита Фаритовна; Исаев В. И. Валерий Иванович; Крутенко Д. С. Даниил Сергеевич; Лобова Г. А. Галина Анатольевна; Меренкова А. С. Анна Сергеевна (2020, 2020)
Заглавие с экрана